Behavior’s study of psychrotrophic microorganisms isolated from cooled raw milk - Goulart, Juliana; Prado, Poliana Cristiane do; Matias, Carolina Laipelt; Pinto, Andrea Troller (Pubvet, 2022)
Milk cooling temperatures facilitate the multiplication of psychrotrophic bacteria that produce thermoresistant enzymes with potential to degrade milk’s components. Aiming to evaluate the behavior of psychrotrophs in cooling raw milk, this study aimed to verify the multiplication and enzymatic activity of milk intentionally contaminated with such microorganisms at refrigeration temperature. Also, it was intended to evaluate the enzymatic activity during long pasteurization (LTST). For this, proteolytic psychrotrophs were isolated from refrigerated raw milk. These microorganisms were tested for their generation time at a temperature of 7 ± 1° C for 192 hours in two different media: Brain Heart Infusion broth (BHI) and 10% reconstituted skim milk (LCR). They were also evaluated for the production of proteases and their respective enzymatic activities during slow pasteurization. The results demonstrated that the isolates did not reach the stationary phase in the bacterial growth curve during the eight days of incubation. Furthermore, proteolytic enzyme activities were detected even after heat treatment, indicating resistance to slow pasteurization temperatures. In conclusion, to avoid economic losses associated with enzymatic activity, it is suggested that there is greater sanitary control of the production environment, as well as reduced storage periods prior to thermal processing, in order to reduce the multiplication of proteolytic psychrotrophs.
Keywords: Enzymatic activity; growth curves; long pasteurization